Fitness profile of elite Croatian female taekwondo athletes - Markovic, G.; Misigoj-Durakovic, M.; Trninic, S. (Collegium Antropologicum, 2005)
The aim of the study was to assess fitness profile of elite Croatian female taekwondo athletes and to determine which physical, physiological and motor characteristics differentiate mostly the successful from the less successful fighters. Thirteen national taekwondo champions were divided into two groups according to their senior international competitive achievements. Physiological characteristics, including maximal oxygen uptake (VO2max), were assessed during a continuous progressive treadmill test. The measured motor abilities included explosive and elastic leg strength, maximal strength, muscular endurance, anaerobic alactic power, agility and flexibility. Differences between the successful and less successful athletes were determined using independent t-test. Even though the differences were not statistically significant, the successful athletes had somewhat less fat (2.3%) and were taller by 5.8 cm. The successful athletes achieved significantly higher maximum running speed (15.8 ± 0.5 versus 14.9 ± 0.7 km h-1; p<0.05), their ventilatory anaerobic threshold was significantly higher (41.4 ± 4.1 versus 37.6 ± 2.0 ml kg-1 min-1; p<0.05) at a significantly lower heart rate (166.8 ± 6.8 versus 171.0 ± 8.2 beats min-1; p<0.05) than in the less successful athletes. Significant differences were also found in three tests of explosive power (p<0.05), anaerobic alactic power (p<0.01), and lateral agility (p<0.05). The performance of taekwondo female athletes primarily depends on the anaerobic alactic power, explosive power expressed in the stretch-shortening cycle movements, agility and aerobic power.